Self-supported electrode of NiCo-LDH/NiCo2S4/CC with enhanced performance for oxygen evolution reaction and hydrogen evolution reaction. (20th January 2021) - Liu, Yuxuan; Bai, Yu; Yang, Weiwei; Ma, Jiahuan; Sun, Kening
Highlights: We present a hierarchical heterostructural electrode constructed by coupling NiCo-LDH nanosheets with NiCo2 S4 nanoneedles through a simple and facile preparation process. The NiCo-LDH/NiCo2 S4 /CC electrode exhibits enhanced bifunctional electrocatalytic performance in alkaline electrolyte for both OER and HER. The hierarchical structure facilitates the exposure of active sites, and the numerous channels in the electrode lead to efficient mass transport and rapid release of bubbles. The phase transformation from NiCo2 S4 to highly active CoOOH and the strong electron coupling between NiCo-LDH and NiCo2 S4 promote the electrocatalytic activity. Abstract: T he exploitation of bifunctional electrocatalysts for stable and efficient water splitting is of great significant for the development of clean energy industry. Herein, a hierarchical NiCo-LDH/NiCo2 S4 /CC electrode is prepared on carbon cloth by coupling NiCo-LDH nanosheets with NiCo2 S4 nanoneedles through a simple process. This NiCo-LDH/NiCo2 S4 /CC electrode serves as an efficient bifunctional electrocatalyst for overall water splitting with excellent activity and stability in alkaline media. The enhanced electrocatalytic performance is ascribed to the hierarchical structure, the synergistic effect of NiCo-LDH and NiCo2 S4 as well as the phase transformation of NiCo2 S4 in alkaline condition. The NiCo-LDH/NiCo2 S4 /CC electrode requires overpotentials of 254 and 219 mV to deliver the current density of 50 mA cm -2 for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in 1 M KOH aqueous solution, respectively. The Tafel results further reveal favorable reaction kinetics during electrolysis. When used as the bifunctional electrode for overall water splitting, the NiCo-LDH/NiCo2 S4 /CC performs superior activity with a voltage of 1.64 V at the current density of 50 mA cm -2 . This work offers a new approach for the exploitation of high-performance and cost-efficient bifunctional catalysts for water splitting. Graphical abstract: More exposure of active sites attributed to hierarchical structure and the synergistic effect between NiCo-LDH and NiCo2 S4 enhance the electrocatalytic performance for both OER and HER. Image, graphical abstract